THE LEGISLATION OF THE REPUBLIC OF KAZAKHSTAN, REGULATING FACTORING RELATIONSHIP - Aizhan Zingaleevna, Амангалиева (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This article is devoted the legal bases of one of the types of financing receivable financing - factoring. The author analyzes the process of formation and development of the legislation of Kazakhstan on factoring. The article examines the international acts, the legislation of the Republic of Kazakhstan that regulate factoring business. Also, provides a comparative characteristics of legislation of the Russian Federation and the Republic of Belarus in sphere of regulation of factoring relations.